1996
DOI: 10.1007/bf00189183
|View full text |Cite
|
Sign up to set email alerts
|

The genesis of Colombian emeralds: a restatement

Abstract: A renewal of metallogenetical studies of Colombian emerald deposits produced new geological and geochemical data that favour a hydrothermal-sedimentary genetic model for these deposits. A comprehensive model is presented which integrates both chemical and structural aspects and invalidates some aspects of the model recently presented by Ottaway et al. The deposits result from a two-stage process in which shortening tectonics affect the two borders of the Eastern Cordillera of Colombia and provoke decollement p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…An idealized Type IA (tectonic-magmatic-related The deposits are unusual because there is no evidence of magmatic activity. Instead, the emeralds formed as a result of hydrothermal growth associated with tectonic activity (Ottaway et al, 1994;Giuliani et al, 1995;Cheilletz and Giuliani, 1996;Branquet et al, 1999a,b). The parent fluids are thought to have formed at depth from meteoric and formational water interacting with salt beds and evaporitic sequences (Ottaway et al, 1994;Giuliani et al, 2000).…”
Section: Country Rockmentioning
confidence: 99%
“…An idealized Type IA (tectonic-magmatic-related The deposits are unusual because there is no evidence of magmatic activity. Instead, the emeralds formed as a result of hydrothermal growth associated with tectonic activity (Ottaway et al, 1994;Giuliani et al, 1995;Cheilletz and Giuliani, 1996;Branquet et al, 1999a,b). The parent fluids are thought to have formed at depth from meteoric and formational water interacting with salt beds and evaporitic sequences (Ottaway et al, 1994;Giuliani et al, 2000).…”
Section: Country Rockmentioning
confidence: 99%
“…SAA18 Interpretation / November 2015 restricted in outcrop (e.g., in the Upín salt mine and La Campana salt layers west of Restrepo, Figure 1, and the emerald-bearing evaporitic layers of Chivor, Gachala and El Toro;Cheilletz and Giuliani, 1996;Branquet et al, 2002;Mora et al, 2009).…”
Section: Tectonostratigraphic Evolutionmentioning
confidence: 99%
“…In the Guateque-Medina area, north of the study area, a brecciated evaporitic layer below the Macanal Formation hosts emeralds and gypsum deposits ( Figure 6) (Cheilletz and Giuliani, 1996;Branquet et al, 2002), in which fluid-inclusion studies revealed Na-Ca-K-bearing hypersaline chlorine brines responsible for emerald and pyrite crystallization by deep-seated formation waters heated by burial, thereafter dissolving evaporites by interaction with salt diapirs (Giuliani et al, 1995).…”
Section: Evidence For Salt Tectonicsmentioning
confidence: 99%
“…There are three end-member genetic types of solid bitumens, solid bitumens from biodegradation and oxidation of crude oils (Tissot and Welte, 1984), solid bitumens from thermal cracking of crude oils (Hunt, 1996;Isaksen, 2004) and solid bitumens from thermochemical sulfate reduction (Sassen, 1986;Heydari, 1997;Machel, 1987Machel, ,2001Leventhal, 1990;Cheilletz and Giuliani, 1996;Giuliani et al, 2000). The LSLR bitumens in the nonmarine sandstone reservoirs in the Xujiahe Formation most probably resulted from the thermal cracking of crude oils, whereas the HSHR bitumens in the marine carbonate reservoirs were the combined product of thermal cracking of crude oils and thermochemical sulfate reduction, and should be considered to be pyrobitumens (Sassen, 1986).…”
Section: Distribution and Genetic Types Of Solid Bitumensmentioning
confidence: 99%